On the disintegration of cosmic ray nuclei by solar photons - Epele, Luis Nicolás (1999)
We discuss in detail the possibility of observing pairs of simultaneous parallel air showers produced by the fragments of cosmic ray nuclei which disintegrated in collisions with solar photons. We consider scenarios with different cosmic ray compositions, exploring the predicted rates for existing and planned detectors and looking for methods to extract information on the initial composition from the characteristics of the signal. In particular, we find that fluorescence detectors, such as HiRes or the Telescope Array, due to their low threshold ( ~ 1017 eV) and large area ( ~ 104 km2) may observe several events per year if cosmic rays at those energies are indeed heavy nuclei. The possibility of exploiting the angular orientation of the plane containing the two showers to further constrain the cosmic ray composition is also discussed.